Molecular Profiles of Five Salinity-Resistant Soybean {glycine max (L.) Merr.} Cultivars - Juwarno Juwarno; Hartanto Nugroho; Triani Hardiyati; Alice Yuniaty (Molekul, 2020)
In this study, the molecular profiles of five soybean cultivars (Burangrang, Gema, Grobogan, Panderman, and Sinabung) exhibiting salinity resistance were elucidated. The DNA profiles of the five cultivars were found to differ based on simple sequence repeat (SSR), insertion-deletion polymorphism (InDel)-QS080465, and sequence characterized amplified region (SCAR)-QS08064 markers. Three distinct SSR profiles¾Satt-243, Satt-294, and Satt-308¾and the SCAR-QS08064 marker were only observed in the Grobogan cultivar, whereas the InDel-QS080465 marker was only successfully amplified from the Burangrang, Gema, and Grobogan cultivars. The results indicate that the Grobogan cultivar is the most tolerant soybean cultivar, followed by the Burangrang and Gema cultivars. Results were consistent with those from genetic similarity analysis, which showed that Grobogan is genetically more similar to Burangrang and Gema compared to Sinabung and Panderman. In conclusion, the five soybean cultivars have different molecular profiles that are related to their resistance to salinity. SSR markers, InDel QS080465-152, and SCAR QS08064-383 are molecular markers specific to salinity-resistant cultivars.